Changes in protein expression profiles in bovine endometrial epithelial cells exposed to E. coli LPS challenge. Issue 2 (10th January 2017) - Piras, Cristian; Guo, Yongzhi; Soggiu, Alessio; Chanrot, Metasu; Greco, Viviana; Urbani, Andrea; Charpigny, Gilles; Bonizzi, Luigi; Roncada, Paola; Humblot, Patrice
Abstract : Proteomics of the physiological response of bEECs to LPS challenge to unravel the possible implication of bacterial infection in pregnancy establishment. Abstract : E. coli is one of the most frequently involved bacteria in uterine diseases. Lipopolysaccharide (LPS) is a component of the outer membrane of Gram-negative bacteria involved in pathogenic processes leading to post-partum metritis and endometritis in cattle. It also causes inflammation of the endometrium. The increase of cell proliferation by LPS is part of the inflammatory process. The aim of this study was to investigate possible changes in protein expression in relation to the proliferative response of bEECs after challenge with E. coli -LPS. In vitro culture of bEECs was performed from cow genital tracts collected at a slaughterhouse. In passage 5, bEECs from each of 9 cows (3 series of 3 cows) were exposed to 0, 8, and 16 μg ml −1 LPS for 72 h. At time 0 and 72 h later, attached cells/living cells were counted and for each time and LPS dosage, cells were frozen for proteomic analyses. All samples from the 3 series were analyzed by 2-D gel electrophoresis coupled to MALDI-TOF/TOF mass spectrometry. The samples from the first series were subjected to shotgun nLC-MS/MS analysis. From the whole differential proteomics analysis, 38 proteins were differentially expressed ( p < 0.05 to p < 0.001) following exposure to LPS. Among them, twenty-eight were found to be up-regulated in the LPS groups in comparison to control groups and ten were down-regulated. Differentially expressed proteins were associated with cell proliferation and apoptosis, transcription, destabilization of cell structure, oxidative stress, regulation of histones, allergy and general cell metabolism pathways. The de-regulations induced by LPS were consistent with the proliferative phenotype and indicated strong alterations of several cell functions. In addition, some of the differentially expressed proteins relates to pathways activated at the time of implantation. The specific changes induced through those signals may have negative consequences for the establishment of pregnancy.